Development of a Prototype Web-Based Information System for Home Visit Services at Puskesmas Kemang, Bogor Regency - Irjayanto , Pratama Gustia; Fery Fadly; Junaedi, Fadil Ahmad (Poltekkes Kemenkes Tasikmalaya, 2025)
Background: Home Visit is one of the healthcare programs at Puskesmas Kemang, serving as a supporting activity for counseling and guidance to obtain data, information, and commitment in resolving patients’ health problems through home visits. Interviews with cadres and nurses revealed that the implementation of Home Visit is still carried out manually, resulting in services that are less efficient and slower. Considering the increasing demand for patient-centered care and the limited use of health information technology at the Puskesmas, an information system is needed to accelerate and streamline the service process with accurate data output. This study aims to design a prototype of a web-based Home Visit information system at Puskesmas Kemang, Bogor Regency. Methods: The study applied the System Development Life Cycle (SDLC) with a Waterfall model. Data were collected through interviews and direct observation. Results: The current Home Visit service is still performed manually without a standardized Standard Operating Procedure (SOP), causing delays and unstructured workflows in registration, examination, and documentation. The designed prototype aligns with service needs and provides a more systematic workflow. Conclusion: The absence of SOPs in the Home Visit program has reduced service efficiency. The proposed web-based information system proves effective in accelerating registration, simplifying visit documentation, and improving the organization of patient records. Thus, this system is expected to enhance the quality of health services at Puskesmas Kemang by supporting the transition from manual processes to standardized electronic systems.